2011
DOI: 10.1261/rna.2593211
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of highly conserved bases in the peptidyltransferase center induce compensatory rearrangements in yeast ribosomes

Abstract: Molecular dynamics simulation identified three highly conserved rRNA bases in the large subunit of the ribosome that form a three-dimensional (3D) ''gate'' that induces pausing of the aa-tRNA acceptor stem during accommodation into the A-site. A nearby fourth base contacting the ''tryptophan finger'' of yeast protein L3, which is involved in the coordinating elongation factor recruitment to the ribosome with peptidyltransfer, is also implicated in this process. To better understand the functional importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…The hybrid corridor is analogous to the accommodation corridor that we previously identified, 46 for which the constituent molecular interactions have been experimental corroborated. [65][66][67][68][69] …”
Section: Cca Movement Is Associated With An Intermediate Ensemble Andmentioning
confidence: 99%
“…The hybrid corridor is analogous to the accommodation corridor that we previously identified, 46 for which the constituent molecular interactions have been experimental corroborated. [65][66][67][68][69] …”
Section: Cca Movement Is Associated With An Intermediate Ensemble Andmentioning
confidence: 99%
“…A computer simulation of the accommodation pathway revealed that nucleotide U2473 (E. coli numbering/mouse U4071) in H89 makes direct contacts with the elbow region of the aa-tRNA in the early stages of the A/T to A/A transition and continuously associates with the backbone of the aa-tRNA throughout this process (27). Yet another simulation showed that H89 is displaced during accommodation, and it was suggested that residues in this helix can acquire alternative conformations for different aa-tRNAs (36,37). Comparison of x-ray structures of the 70 S ribosome with cognate or near cognate tRNA reveal a network of rRNA helices (including H89) and ribosomal protein contacts that stabilize the elbow of cognate tRNA in the A/A state (38).…”
Section: Discussionmentioning
confidence: 99%
“…1 Many mutants of the peptidyl transferase region of ribosome have been reported in the literature. [1][2][3][4][5][6][7][8] The most widespread phenotype was reduction in puromycin reactivity, while inability to catalyze the peptidyl transferase reaction involving natural tRNA substrates was scarce. 1 Nevertheless, the majority of those mutations were lethal when tested in vivo.…”
Section: Introductionmentioning
confidence: 99%